Výroba ukazatele hladiny technologií přesného stříhání - Polák, Pavel (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
Projekt vypracovaný v rámci inženýrského studia oboru 2307 předkládá návrh technologie výroby plechové součásti ukazatele hladiny stříháním ocelového plechu 11 373.1. Střihadlo využívá normalizovaných komponent a je řešeno formou obvyklého stojánku upnutého na klikovém tažném výstředníkovém lisu LEN 63 C (výrobce APJ Praha), s nominální tažnou silou 630 kN. Tažník a tažnice jsou vyrobeny ze slitinové nástrojové oceli 19 436.9 (POLDI 2002), tepelně zpracované podle výkresové dokumentace.

The project elaborated in frame of engineering studies branch 2307. The project is submitting design of technology production of the extract - section from the deep drawing sheet iron 11 373.1. Pursuant to of the literary pursuit a problem of the deep drawing and calculation was designed drawing in instrument with holder. The lower ejector is using for extrusion component. The drawing instrument make use of standardised components and it is solving forms of customary stool close-set on the crank drawing inclinable press LEN 63 C (producer APJ Praha), with nominal tensile force 630 kN. Drawing punch and drawing die are produced from alloyed instrumental steel 19 436.9 (POLDI 2002), heat-worked according to drawing documentation.
The manufacturing of level indicator by fineblanking process
Keywords: Ocel 19 436; tváření; mezní přetvoření; tažení; 19 436 steel; forming; deep drawing; forming limit diagram